2021
DOI: 10.3390/su13074036
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Visitors at an Urban Park by Profiling of Destination Attributes

Abstract: A park has a variety of attributes, providing beautiful natural scenery and a place to rest as well as a cultural space in which performances and events are held. This study aimed to examine the various destination attributes that a place has, specifically, the resources of an urban park, by profiling visitors according to these destination attributes. The study setting, Gwanggyo Lake Park (GLP), is located in Suwon City and is in the limelight as an eco-friendly leisure and tourism destination in South Korea.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Notably, environmental GI, which indicates individual recognition of biodiversity, ecosystems, and green stewardship, plays a significant role in the GI-GSP relationship. This insight aligns with increasing attention toward urban nature in South Korea's capital region, ranging from individual (Baek et al, 2020) to political efforts by local governments (Choi and Kim, 2022). Baek et al (2020) found that urban residents' desire to engage with nature correlates strongly with their intention to visit greenspaces.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Notably, environmental GI, which indicates individual recognition of biodiversity, ecosystems, and green stewardship, plays a significant role in the GI-GSP relationship. This insight aligns with increasing attention toward urban nature in South Korea's capital region, ranging from individual (Baek et al, 2020) to political efforts by local governments (Choi and Kim, 2022). Baek et al (2020) found that urban residents' desire to engage with nature correlates strongly with their intention to visit greenspaces.…”
Section: Discussionmentioning
confidence: 64%
“…This insight aligns with increasing attention toward urban nature in South Korea's capital region, ranging from individual (Baek et al, 2020) to political efforts by local governments (Choi and Kim, 2022). Baek et al (2020) found that urban residents' desire to engage with nature correlates strongly with their intention to visit greenspaces. Their study supports the present study's findings that environmental GI has the strongest influence on greenspace perception.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Destination attributes are qualities or characteristics of a destination. They pull visitors to a particular destination and engage in a particular tourist activity (Baek, et al, 2021). Destination attributes will be perceived by the visitor during their visit (Jumanazarov, Kamilov, & Kiatkawsin, 2020), thus reflecting their overall satisfaction (Djeria, et al, 2018;Biswas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Destination attributes will be perceived by the visitor during their visit (Jumanazarov, Kamilov, & Kiatkawsin, 2020), thus reflecting their overall satisfaction (Djeria, et al, 2018;Biswas et al, 2020). Evaluating destination attributes will result in awareness of a destination management organization towards its strengths and weaknesses (Pike & Kotsi, 2018;Djeria, et al, 2018;Jumanazarov, Kamilov, & Kiatkawsin, 2020;Baek, et al, 2021), thus providing them with the ability to develop strategies to cope with the weaknesses, and improve the satisfaction of its visitors.…”
Section: Introductionmentioning
confidence: 99%